PENERAPAN METODE PEMBELAJARAN REFLECTIVETHINKING DENGAN PENDEKATAN BERORIENTASI PERTANYAAN DAN BRAINSTORMING PADA MATA KULIAH MEKANIKA - Fajar fitri (Universitas Sriwijaya, 2016)
Abstract: Technology is developing very fast nowadays. It creates so many effects - wether the effects are posssitive effects or negative effects. College students should have the ability to choose, analyze, and filter the technology and its development so that it affects their lifesinpossitiveway. Because of that, college students should have the critical thinking skills so they can solve any kinds of problems in theirlifes. In Mechanics, college students need to develop their ability to think how to solve the problems of the evironments. The purpose of this research is to know and compare the activism and the critical thinking skillsof the college students after they implemented the Reflective Thinking learning method with an appproachment that oriented in question and brainstorming in Mechanics. The method of this research is quasi experimental. The sample of this research is college students of the Physics Education Program in first semester of the 2015/2016 school year that were learning Mechanics. The research was done in two classes,wich in each class was given a learning with Reflective Thinking. Class A with an appproachment that oriented in questions and class B with brainstorming. Observation was done to know the level of the activism and the critical thinking skillsof the college students. The result of each class was compared to another class so we could knowwich class that showed the greatest level of the activism and critical thinking skills of the college students.Based on research, we could conclude that the level of the critical thinking of the students in Reflective Thinking learning method with an appproachment that oriented in question is higher than the students in critical thinking skills learning method with an appproachment that oriented in brainstorming. Meanwhile the level of the activism of the students in Reflective Thinking learning method with an appproachment that oriented in brainstorming is higher than the students in Reflective Thinking learning method with an appproachment that oriented in question